DUKUNGAN SOSIAL, PEKERJAAN DAN ADIKSI MENENTUKAN PERILAKU SEKS PRANIKAH - Tenri, Andi; Khoiriyah, Imas Elva; Fatah, Mohammad Zainal (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Adolescence is a period of transition from children to adults. This causes adolescents to experience many challenges, namely the three risks that are often experienced by adolescents (TRIAD KRR) namely risks related to sexuality (unwanted pregnancy (KTD), abortion and infection with sexually transmitted diseases, drug abuse, and HIV/AIDS). only premarital sex behavior. There are several factors that can cause premarital sexual behavior in adolescents, including sexual urges from adolescents, parental control, knowledge about reproductive health, wrong understanding of dating, the desire to try, exposure to information media, influence peers and others. Using scoping review with a total of 25 articles from both international and national articles. Data collection was carried out in 3 databases, google scholar, PubMed and Sciendirect with the keywords "Reason of premarital sex", "decision making of premarital sex” and “reasons for premarital sex”. Articles consist of articles international and national with a time span of 2017-2021 An overview of the results of the research conducted. There are 4 assumptions that underlie the perpetrators in making the decision to have premarital sex, including the assumption about love that makes them feel lucky to be loved, the assumption that peer influence makes them luckiest if they follow their friends, the assumption of economic benefits by assuming that sexual behavior is the easiest way getting material which makes the economy better, and assuming non-material benefits in the form of good grades or academic relation.